2014
DOI: 10.1016/j.electstud.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A perfect match? The impact of statement selection on voting advice applications' ability to match voters and parties

Abstract: A perfect match? The impact of statement selection on voting advice applications' ability to match voters and parties Lefevere, J.M.; Walgrave, S. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…This means that the design choices in VAAs have a substantial impact on the outcome. There are other studies that have shown that such design effects also occur as a result of other elements of the design, such as statement selection (Lefevere & Walgrave, ; Walgrave et al, ). In this article we have expanded this strand of research by analyzing the relevance of the response scale format that VAAs employ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the design choices in VAAs have a substantial impact on the outcome. There are other studies that have shown that such design effects also occur as a result of other elements of the design, such as statement selection (Lefevere & Walgrave, ; Walgrave et al, ). In this article we have expanded this strand of research by analyzing the relevance of the response scale format that VAAs employ.…”
Section: Discussionmentioning
confidence: 99%
“…VAAs are well‐known and widely used in many countries today (for reviews about their history and usage, see Cedroni & Garzia, ; Garzia & Marschall, ), and research about the design, purpose, and effects of VAAs has matured in recent years (see, e.g., Garzia & Marschall, ; Rosema, Anderson, & Walgrave, ). The topics addressed in research about VAAs are diverse and include, among others, the selection of statements (Lefevere & Walgrave, ; Walgrave et al, ), the coding of party positions (Gemenis, ; Gemenis & van Ham, ; Trechsel & Mair, ), and the spatial models used in VAAs (Germann, Mendez, Wheatley, & Serdült, ; Louwerse & Otjes, ; Otjes & Louwerse, ). These are all elements of the design of VAAs.…”
Section: Introductionmentioning
confidence: 99%
“…It goes almost without saying that the quality of euandias in any other VAA endeavour, for that mattersdepends first and foremost on the content and formulation of its statements (Walgrave et al, 2009;Lefevere and Walgrave, 2014;Van Camp et al, 2014). This task was undertaken in close collaboration with the International Advisory Board of euandi.…”
Section: The Euandi Questionnairementioning
confidence: 99%
“…Concerning the selection and formulation of statements, early research has provided clear evidence that the choice and composition of statements make a difference to the result indicated by a VAA (Lefevere & Walgrave, , ; Walgrave, Nuytemans, & Pepermans, ). The same seems to apply to the formulation of the statements; responses to the statements vary according to how they are formulated, for example, whether they are put positively or negatively (Holleman, Kamoen, van de Pol, Krouwel, & de Vreese, ; Van Camp, Lefevere, & Walgrave, ).…”
Section: The Proliferation Of Vaa Researchmentioning
confidence: 99%